Quantitative analysis for management. - Render, Barry; Stair, Ralph M.; Hanna, Michael E. (Upper Saddle River, N.J. : Pearson Prentice Hall, 2008)
Render/Stair/Hanna puts an emphasis on model building and computer applications to show students how the techniques presented in the text are used in business. This text$1 (Bs use of software also allows instructors to focus on the managerial problem, while spending less time on the mathematical details of the algorithms. In the eleventh edition, Excel 2010 has been incorporated throughout the text and an even greater emphasis on modeling is provided.s
Chapter 1. Introduction to Quantitative Analysis -- Chapter 2. Probability Concepts and Applications -- Chapter 3. Decision Analysis -- Chapter 4. Regression Models -- Chapter 5. Forecasting -- Chapter 6. Inventory Control Models -- Chapter 7. Linear Programming Models: Graphical and Computer Methods -- Chapter 8. Linear Programming Applications -- Chapter 9. Transportation and Assignment Models -- Chapter 10. Integer Programming, Goal Programming, and Nonlinear Programming -- Chapter 11. Network Models -- Chapter 12. Project Management -- Chapter 13. Waiting Lines and Queuing Theory Models -- Chapter 14. Simulation Modeling -- Chapter 15. Markov Analysis -- Chapter 16. Statistical Quality Control.
Includes bibliographical references and index.
Keywords: Management science; Operations research